Sex Differences in Susceptibility to Coccidioidomycosis. (16th February 2022) - McHardy, Ian; Reagan, Krystle L; Sebastian, Jamie F; Barker, Bridget; Bays, Derek J; Dandekar, Satya; Cohen, Stuart H; Jennings, Kathleen E; Sykes, Jane; Thompson, George R
Abstract: To assess sex-specific differences in coccidioidomycosis, a retrospective analysis of human patients, nonhuman primates, and veterinary patients (including the neutered status of the animal) was performed. We found higher rates of infection and severity in males. This observed increased infection risk suggests deeper biological underpinnings than solely occupational/exposure risks. Abstract : An evaluation of human, non-human primates, and veterinary animals was performed to evaluate for sex-specific differences in the rate of acquisition, and severity of coccidioidomycosis.  Higher rates of infection and severity was observed in males across all species.